The research potential of A20 in psoriatic arthritis - Wan, Yixuan Wang; Duan, Xiaoru; Jin, Zilin; Chen, Hongxiang (Frontiers in Immunology, 2026)
Psoriasis, a systemic inflammatory disorder, extends beyond its classical dermatological presentation to encompass multiple manifestations including arthritis, inflammatory bowel disease, ocular inflammation (conjunctivitis/uveitis), and cardiovascular manifestations such as aortic valve pathology. While cutaneous manifestations have been extensively characterized, psoriatic arthritis (PsA) remains challenging to investigate, primarily due to the paucity of suitable experimental models that accurately recapitulate human disease. The ubiquitin-editing enzyme A20 (encoded by TNFAIP3) emerges as a critical regulatory molecule, serving dual functions in suppressing NF-κB signaling pathways and modulating programmed cell death mechanisms. Genome-wide association studies have established TNFAIP3 polymorphisms as susceptibility loci for both psoriasis and PsA. Murine models with A20 deficiencies demonstrate spontaneous development of cutaneous psoriasiform lesions and articular inflammation, with genetic manipulation techniques generating diverse mutation patterns that manifest in heterogeneous phenotypes. Systematic analysis of these preclinical models offers valuable insights into the molecular pathogenesis of PsA, potentially bridging current knowledge gaps in disease mechanisms and therapeutic target identification.